Potential of Therapeutic Ethanolic Extract of Flavonoids Mutingia Calabura on Alloxan-induced Diabetic Male Mus musculus - Rahayu, Zilfia; Rahmayanti, Wulan Desi; Tanjaya, Steve Pratama; Aziz, Nanda Putri Utami; Christian, Samuel Erza; Ridwan, Sucilawaty; Hidayat, Lalu Husnul (Jurnal Biologi Tropis, 2025)
One alternative treatment for diabetes mellitus is herbal therapy. One example of herbal therapy that can be used to treat diabetes mellitus is cherry. Cherry (Muntingia calabura L.) is a plant that is widespread in Indonesia, including NTB. In West Nusa Tenggara, cherry plants are very abundant and can often be found on roadsides and in house yards. One of the compounds contained in cherry leaves which has antidiabetic and antioxidant activity is flavonoids. The aim of this research was to determine the potential of ethanol flavonoid extract to reduce blood sugar levels in mice induced by alloxan. The manufacture of cherry leaf ethanol extract was carried out using the sonication method, with the testing process including qualitative tests, quantitative tests, evaluation of cherry leaf ethanol extract suspension preparations, and measurement of fasting blood sugar. The results of blood sugar measurements showed that administering a dose of 300 mg/kg showed the best results which were almost the same as the positive control (metformin).